Common Hemoglobinopathies for Couples Premarital Individual and its Influence on Hemostasis and Immune State (Medico Legal Update, 2021)
Before marriage, couples are screened through a procedure known as premarital screening for differentgenetic, infectious or bloodborne diseases that can be passed from them to their offspring. The aim of ourresearch was to assessment the premarital screening of couples for hemoglobinopathies and undiagnosedcases with suggestive findings of thalassemia or its variants. and evaluation hematology parameters amongcommon Hb hemoglobinopathy. This study contains 228 individuals with hemoglobinopathy, the participantswere couples attending primary health centers for regular premarital inquiries in baquba teaching hospitals,Iraq. ?-thalassemia was enrolled in 3 (1.3%) from all hemoglobinopathy individuals, ?-thalassemia wasenrolled in 255 (98.8 %), which include ?-thalassemia minor in 226 individuals 88.6%, while ? thalassemiaintermediate in 5 individuals 2.2% from all individuals with hemoglobinopathy Figure 1 and 2. Othersthalassemia was recorded 3 Hb-E 1.1%, 1 Hb-S 0.39, 10 Hb-D 3.92, 13Hb-C 5.09. Pre-marital examinationsare important to determine hemoglobinopathy and limit transmission to offspring, as well as blood tests areimportant to identify people with haemoglobinopathy and its influence.